Biogas production of pineapple juice and fibres through anaerobic digestion / Haris Imran Ahmad Marzuki ...[et al.] - Ahmad Marzuki, Haris Imran; Shazali, Ahmad Syazwan; Syed Osman Al Haddad, Syed Ahmad; Sukor, Mohd Zaki
The biogas production of pineapple juice and fibres are conducted through the process of anaerobic digestion. The experiment was conducted with various ratios of pineapple fibres to pineapple juice. In this experiment, municipal waste acted as inoculum which is the source of microbial organisms such as bacteria. The reaction of inoculum with the substrates was experimented for 21 days and showed no displacement of water level in the test tube. Municipal waste is not effective to act as an inoculum for anaerobic digestion of pineapple juice and fibres to produce biogas through the observation. Thus, several causes of failure has been identified which is based on the inoculums used, size of bioreactor, and pH of the mixture.